The Cost of Inaction : Can We Afford Not to Invest in Road Safety? - Bose, Dipan; Marquez, Patricio V.; Job, Soames (World Bank, Washington, DC, 2018)
Road crashes are among the most significant public health issues of the century; they account for 97 percent of deaths across all modes of transport. The latest WHO estimate of 1.34 million road crash deaths and up to 50 million injuries per year reflects a slight increase in deaths over previous years, with 90 percent of these deaths occurring in low and middle-income countries. Further road injury disproportionately affects young adults 15–29 years old: it is the lead cause of death during their most productive years. Along with the unquantifiable loss of life, and pain,grief and suffering, there is a direct burden to society from disabilities, deaths, and the economic hardships they bring. The devastating impact is not only felt by the victim’s family, where the disability or death of a breadwinner can drive a household into poverty; it also affects the overall economy. Overall productivity and quality of life is affected when otherwise healthy individuals are disabled or die. Crashes also place a burden on emergency response, medical treatment, and rehabilitation services in addition to loss of labor productivity, affecting the quality of life of the overall population.